A Gain Design Strategy for an Active Damping Controller of a MIDP Permanent Magnet Synchronous Motors Drive System - Nam, Gi Jung; Lee, Hyung Woo; Lee, Kyo Beum (2024 IEEE Energy Conversion Congress and Exposition, ECCE 2024 - Proceedings, 2024)
This paper proposes a gain design strategy for an active damping controller in a mono-inverter dual parallel (MIDP) permanent magnet synchronous motors (PMSMs) drive system. Dual motors are connected in parallel with a single inverter. One motor is chosen as a master motor which is the main controlled motor and the other motor is chosen as a slave motor which is controlled simultaneously with a master motor. Since a single inverter controls two motors in a MIDP system, torque oscillation occurs in the slave motor. Therefore, an active damping controller that regulates torque oscillations is required. This paper provides a design strategy for a gain of an active damping controller. The performance of the proposed design strategy for a MIDP PMSMs drive system is verified by simulation results with two 500-W PMSMs.
Keywords: A single inverter; Active damping; Damping controllers; Design strategies; Dual motor drive system; Dual-motors; Gain design; Motor drive system; Permanent Magnet Synchronous Motor; Single inverters; A single inverter; Dual motors drive system; Gain design; Permanent magnet synchronous motor